Pengaruh Supervisi, Motivasi Kerja dan Komunikasi terhadap Kinerja Guru SMA Negeri 1 Unaaha - Risman Risman; Ibnu Hajar; Muh. Nur (Jurnal Syntax Admiration, 2024)
This study aims to determine and analyze the influence of supervision, work motivation and communication on the performance of teachers of SMA Negeri 1 Unaaha. The sample in this study was all teachers of SMA Negeri 1 Unaaha totaling 65 people. This study used multiple linear regression analysis. The results showed that: (1) Supervision, work motivation and communication had a positive and significant effect on teacher performance. This means that increasing supervision, work motivation and higher communication will improve the performance of SMA Negeri 1 Unaaha teachers. (2) Supervision has a positive and significant effect on performance. This means that increasing supervision will improve the performance of teachers of SMA Negeri 1 Unaaha. (3) Work motivation has a positive and significant effect on teacher performance. This means that increasing work motivation will increase the performance of teachers of SMA Negeri 1 Unaaha. (4) Communication has a positive and significant effect on teacher performance. This means that the higher communication improvement will improve the performance of SMA Negeri 1 Unaaha teachers.